Adolescent male and female rats show enhanced latent inhibition of conditioned fear compared to adult rats - Perry, Christina J.; John, Ricky; Trinh, Han B.; Richards, Brandon K.; Drummond, Katherine D.; Park, Chun Hui J.; Kim, Jee Hyun (Frontiers in Behavioral Neuroscience, 2025)
IntroductionLatent inhibition is diminished associative memory because of pre-exposure to the conditioned stimulus without any consequences. Latent inhibition likely plays a significant role in the ontogeny of anxiety disorders, contributing to why anxiety disorders are particularly prevalent in adolescence. Therefore, the present study examined latent inhibition of conditioned fear in adolescent and adult rats of each sex. Given that adolescence is associated with deficits in fear extinction, we hypothesized that latent inhibition will be impaired in adolescents compared to adults and expected females to show age-specific estrous cycle effects.MethodsOn day 1, male (Experiment 1) and female (Experiment 2) rats were placed in fear conditioning chambers. Half of the rats received pre-exposure to the tone cue while the other half received nothing. On day 2, all rats were placed back in the same chambers and exposed to three cue-footshock pairings. Latent inhibition was tested on day 3 with 20 presentations of the cue by itself in the same chamber.ResultsWe unexpectedly observed enhanced latent inhibition in adolescents compared to adults in both male and female rats, indicated by lower levels of freezing due to pre-exposure to the cue. Estrous cycle did not affect latent inhibition at any age.DiscussionThese results suggest that benign experience to a cue reduces subsequent conditioning to the cue more potently in adolescence compared to adulthood, which suggests a potential resilience mechanism naturally occurring in adolescence.